Optimization Methods for Optical Ammonia Sensor - Hadi, Manap; Zul, Rasyied; M. S., Najib (2015)
This paper describes an optical sensor system for quantifying ammonia at low concentration. An open path optical technique is used to measure ammonia concentration within the Ultraviolet region. Experimental results describing the operation of the sensor with wavelengths combination technique to optimize the measurement is presented. The results show the sensor is best measuring ammonia concentration at combination wavelengths (around 212 nm) with the Lower Detection Limit of 4.31 ppm and 1 s response time is achieved.